Design and analysis of directional front projection screens. (August 2018) - Piovarči, Michal; Wessely, Michael; Jagielski, Michał; Alexa, Marc; Matusik, Wojciech; Didyk, Piotr
Highlights: Efficient convex optimization of tileable shapes with prescribed reflectance. Design of light efficient cinema screens reflecting light only toward the audience. Up to 3 times brighter screens than high gain cinema silver screens. Arbitrary audience shape with support for split-audience reflections. Graphical abstract: Abstract: Traditional display and screen are designed to maximize the perceived image quality across all viewing directions. However, there is usually a wide range of directions (e.g., toward side walls and ceiling) for which the displayed content does not need to be provided. Ignoring this fact results in energy waste due to a significant amount of light reflected toward these regions. In this work, we propose a new type of front projection screens – directional screens . They are composed of tiny, highly reflective surfaces that reflect the light coming from a projector only toward the audience. Additionally, they avoid "hot-spotting" and can support non-standard audience layouts. In this paper, we describe the design process as well as provide feasibility analysis of the new screens. We also validate the approach in simulations and by fabricating several fragments of big screens. We demonstrate that thanks to the customization, our solution can provide up to three times increased gain when compared to traditional high gain screens and up to eight times higher brightness than a matte screen.